Impact of Metro on Urban Land Transformation - Ar. Annu Sharma (International Journal of Urban Design and Development, 2023)
India is one of the fastest-growing economies in the world and is also the second most populous nation, furthermore it has a rapidly growing urban population owing to which the cities are facing severe problems and challenges related to mobility, congestion, and subsequently pollution. In India, a Mass Rapid Transit System, often known as Metro Rail, is being constructed as the optimum answer for a crowded transit corridor in a big city. MRTS primarily emphasis elements such land usage, land values, accessibility, transport patterns, etc. It acts as a catalyst for urban redevelopment by enhancing convenient mobility to remote areas also. In India, another concept called TOD i.e., Transit Oriented Development has also bought into existence, for the effective use of MRTS where TOD is defined as a concept of effective development through the mediums of compact mixed-use development, pedestrianizing people, and making them uses Non- motorized transport around a central transit stop (such as a train station, light rail or bus stop) Therefore, this study is majorly focusing on the impact of metro urban transformation (land use and socio-economic) around the station called City Park Station, Bahadurgarh through the scale of five attributes naming F.A.R, Land Value Master plan development, Population, Time-saving(last mile connectivity). The pre- and post-metro expansion of the chosen corridor is the sole basis for the technique used in this article.
Keywords: Climate change; Industrial Estate; Pollution; urban development; urbanization